New tag estimator for the dynamic framed slotted Aloha anti-collision algorithm in RFID systems - Chibel, Jalel; Attia, Oussama; Habaebi, Mohamed Hadi; Islam, Md Rafiqul (International Journal of Computer Science, Communication & Information Technology (CSCIT), 2019)
Radio frequency identification (RFID) technology is a wireless identification technique that has been used in many fields. This paper investigates the use of this technology for traffic monitoring which is the backbone of any intelligent transportation system. One of the main issues that face this technology is tag collisions. This study examines the performance of two known anti-collisions protocols: the Basic Framed Slotted Aloha (BFSA) and the Dynamic Framed Slotted Aloha (DFSA). For such application, it was found that the DFSA method outperforms the BFSA method. However, the DFSA method requires the use of tag estimator. For this reason, the study compares also the performance of three tag estimators associated with the DFSA: Vogt, Zhen and Schoute. It is observed that the Vogt method is the best if the number of tags is low, while the Schoute approach is superior for higher value. The study proposes a new hybrid tag estimator that combines the strength of the Vogt and Schoute approaches.